Before, while, and after writing: a study on mother tongue reliance and native language transfer among students at various levels of proficiency - Gai, Meijuan; Ariffin, Kamisah; Ahmad, Badli Esham; Yue, Fang (Universiti Teknologi MARA, 2025)
Writing stands out as an exceptionally effective means for articulating thoughts and emotions, assuming a crucial role in the evaluation of learners’ overall competence and is considered an essential element in English examinations. Nevertheless, the performance of high school students in China frequently fails to meet the anticipated standards in this domain. The influence of native language transfer is proposed as a primary factor contributing to this less-thanideal outcome. This study investigates the influence of native language transfer during the English writing process of high school students. The study employed quantitative research methodology, including a writing test and a questionnaire, and applied transfer theory, comparative analysis, and error analysis theory as the theoretical frameworks. The findings indicate the levels of reliance on the mother tongue and its transfer show differences before, during, and after writing among students with varying levels of second language proficiency. This bears noteworthy pedagogical implications for the development of intervention or remedial programs for high school students.